Heavy metal pollution in selected upland tributaries of Sri Lanka: comprehension towards the localization of sources of pollution. (28th January 2022) - Kodikara, K. A. S.; Lewandowski, S.; De Silva, P. M. C. S.; Gunarathna, S. D.; Madarasinghe, S. K.; Ranasinghe, P.; Jayatissa, L. P.; Dahdouh-Guebas, F.
Abstract: This study aimed to assess the heavy metal (HM) profile of the main upland tributaries of three major rivers, the Mahaweli, the Deduru and the Gin Rivers, which are commonly used for urban water supply in Sri Lanka. The HM profiles of arsenic (As), cadmium (Cd), lead (Pb) and mercury (Hg) were investigated by ICP-MS. Land-use classification was performed to locate the main sources of pollution. Mean pH, TDS and conductivity showed significant inter-site mean differences ( p < 0.001). The mean contents of the HMs, considering all rivers, were observed in the order [Hg] > [As] > [Pb] > [Cd] at the sources and [As] > [Hg] > [Pb] > [Cd] at the river mouths. Particularly, in the Mahaweli River, the mean As content was 0.08 ± 0.05 μg·L −1 and showed an increasing trend from the source to the river mouth. In the Deduru River, the mean Hg content was 0.14 ± 0.15 μg·L −1, and of all rivers studied, the highest content of 0.50 ± 0.17 μg·L −1 was recorded. The Gin River showed significant inter-site mean differences ( p < 0.05) in [Pb], [As] and [Hg]. In all rivers studied, [As] was significantly higher in water samples collected near agricultural lands and urban areas as compared with the other land-use/cover types, which was further proved by a significant positive correlation (coefficient = 0.479, p = 0.0325). We, therefore, emphasized that HM pollution is more likely due to anthropogenic activities in the upper catchment with less lithogenic contamination. However, national water quality management should be further strengthened and new policy enforcement is emphasized. HIGHLIGHTS: Arsenic (As) content was higher at the river mouths. Mercury had the highest mean concentration at the sources. As concentration increased gradually from the source to the river mouth. Agricultural activities could be the source of As addition. Sri Lankan river waters are still safe to be used for drinking purposes.